Development and identifying quantitative and quantities traits for breeding of Samae Dam Chicken (Gallus gallus), Thailand: Diversity of phenotypic characteristics - Wiyabot, T; Kiattinarueyut, S (Journal of the Hellenic Veterinary Medical Society, 2023)
The objectives of this study were to the development and technology transfer for local production of Samae Dam Chicken (Gallus gallus) in Uthai Thani Province, Thailand by studying diversity of phenotypic characteristics in the rearing system. The average age of chickens was eight months, randomly numbered 1,000 in Uthai Thani Province. The results showed that variation of quantitative traits such as body weight, body height, body length, body width, wing length, shank length and toes length, the mean is equal to 3.0±0.25 kg/h, 58.5±0.10 cm, 24.5±0.30 cm, 14.5±0.20 cm 33.0±1.15 cm,10.25±0.5 cm and 5.75±0.45 cm respectively. The relationship between qualitative characteristics found that significant strong positive relationships between beak color and shank color (r=0.70; p<0.01), between necklace color and wings feather color (r=0.60; p<0.05), between necklace color and back- necklace color (r=0.15; p<0.01), between wings feathers color and necklace color (r=0.60; p<0.01), between wings feathers color and back-necklace color (r=0.25; p<0.01), between back-necklace color and necklace color (r=0.20; p<0.01), between back-necklace color and wings feather color (r=0.25; p<0.05) and between shank color and beak color. The relationship between quantitative characteristics all positive relationships among the studied quantitative traits was significant (r=0.30 to 0.55; p<0.01). The relationship between qualitative and quantitative factors in which the relationship between characteristics is significant (p<0.05). The positive correlation of beak color with body height (r=0.14), necklace color with bodyweight (r=0.15), necklace color with body width (r=0.17), wings feather color with body length (r=0.23), wings feather color with body width (r=-0.20), wings feather color with wing length (r=-0.14), tail feathers type with bodyweight (r=-0.25), tail feathers type with body height (r=-0.19), tail feathers type with body length (r=-0.26), tail feathers type with body width (r=-0.12), tail feathers type with wing length (r=-0.14), tail feathers type with shank length (r=-0.22), shank color with bodyweight (r=-0.22), shank color with body height (r=-0.18) and shank color with body length (r=-0.22). Effects of qualitative characteristics on quantitative characteristics of the chicken necklace color, wings feather color, back necklace color tail feathers type, shank color had significant difference (p<0.05).